A Lexical Choice of Euphemism in Obituaries in Daily Nation Newspaper - Ogola, Consolata; Njuki, Peter; Kabare, Timothy (International Journal of Linguistics, 2025)
Purpose: The aim of the study was to explore how euphemistic language is used in obituary writing, focusing specifically on the predominant euphemistic expressions used to publish obituaries in Kenyan Daily Nation newspaper. Methodology: The study employed the Mixed Method Research Design. The Quantitative Approach through Corpus Sampling enabled the researcher to collect numerical data from obituaries in the Daily Nation newspaper and established the common euphemisms in these obituaries that affect the reader. Likewise, a Quantitative Approach via Questionnaires aided the researcher in identifying the highly recommended euphemisms for use in obituaries so as to soften the impact of death on the reader. The also applied Qualitative Design through semi-structured interviews. The study drew on three sources: a content analysis of 144 obituaries randomly selected from Daily Nation newspaper publications from 2020 - 2022; 108 completed questionnaires collected from students and staff both teaching and subordinate of Tangaza University; and 10 in-depth interviews with individuals who had experienced the loss of a close family member. Findings: The obituary analysis revealed a strong preference for euphemistic and respectful language in reporting death. Among the most frequently used verbs and phrasal verbs were ―passed on‖ appearing 39 times out of 144 collected obituaries. This made (27.1%) of the total obituaries, ―demise‖ 25 times (17.4%), ―promotion to glory‖11 times (7.64), and ―passed away‖ 5 times (3.47%). ―Promotion to glory‖ appeared as a standalone phrase 21 times (14.6%), while ―humble acceptance of God‘s will‖ 19 times (13.2%) and ―celebration of a life well lived‖ 18 times (12.5%). Secondly, euphemisms provide emotional and psychological relief, acting as a linguistic cushion that allows people to cope with grief in a gentler way. Instead of confronting the harsh reality implied by direct terms like ―died‖ or ―was killed,‖ mourners are given softer language that eases the sense of loss and supports the healing process. Again, the use of euphemistic language in Kenyan obituaries revealed a profound cultural and religious awareness. The phrases commonly found in death announcements aligns with Christian and African worldviews that interpret death as a passage rather than a finality. Words such as ―celebration of life‖ and ―gone to be with the Lord‖ embody communal values and shared beliefs in the continuity of the human spirit. Additionally, these expressions carry spiritual significance, reaffirming collective faith in an afterlife and providing reassurance to the bereaved that their loved ones have journeyed on to another life. For many respondents, euphemisms are not simply linguistic softeners, they are affirmations of hope, belonging and Divine order. Similarly, the study found that euphemisms play a vital role in preserving social and linguistic sensitivity. Unique Contribution to Theory, Practice and Policy: The study was anchored on Politeness Theory by Penelope Brown & Stephen Levinson (1987). In a setting where grief is both personal and shared, such language helps maintain respect, honor the memory of the departed and express compassion for the bereaved. The study suggests that media practitioners and newspaper editors promote the use of emotionally intelligence and culturally sensitive euphemistic language in crafting obituaries in the Daily Nation newspaper. It also recommends that the family writing obituaries to choose expressions that reflects the spirit, beliefs, values and personality of the deceased. Likewise, the study recommends the introduction of euphemisms analysis into language and literature curricular as a tool for teaching stylistics and disclose analysis.